E-TEP surgery for ventral hernias: A novel and effective approach to postoperative analgesia - Daniel Mariano de Andrade; Fernando Ponce Leon; Nathalia Barros Oliveira Santos; Jessica Pereira Manso; Luisa Delegave Penedo; Matheus Wanderley Cunha Fernandes Costa; Arnaldo Couto; Fernando Athayde Veloso Madureira (International Journal of Abdominal Wall and Hernia Surgery)
INTRODUCTION: Ventral hernia (VH), associated with diastasis rectus abdominis, is a relatively common pathology in general surgery. Extended-view Totally Extraperitoneal Technique (e-TEP) is a promising surgical technique for its correction. However, it requires extensive dissection and, therefore, can cause postoperative pain. The aim of this study is to propose a new technique for analgesia and to compare it to existing techniques. MATERIALS AND METHODS: Thirty patients were submitted to VH and diastasis correction surgery applying e-TEP technique and randomly divided into three groups, according to the type of analgesia administered: general anesthesia (GA) alone; GA and TA plane block guided by ultrasound (US-TAPB); GA and TAPB by direct laparoscopic view (DV-TAPB). Pain scores using the Numeric Rating Scale were collected at 2, 6, and 24 h postop. The time to administer local anesthetic (LA) was also measured. RESULTS: No significant differences for gender, age, or body mass index (BMI) were observed, nor for the mean defect area and diastasis length, mesh size, and operation time between groups. The DV-TAPB group presented the lowest pain scores at 2 h (P = 0.001), 6 h (P = 0.02), and 24 h (P = 0.01) postoperatively. Additionally, the mean time required to administer the LA was significantly lower in the DV-TAPB group (1.9 min) compared to the US-TAPB group (11.8 min). CONCLUSION: E-TEP is a relatively new and promising technique to treat VH and diastasis. Additional analgesia by DV-TAPB is faster and offers better pain relief in the first 24h postop period. TRIAL REGISTRATION: http://isrctn.org/ (identifier: ISRCTN11379598).